A viscous‐to‐brittle transition in eruptions through clay suspensions. Issue 10 (27th May 2017) - Schmid, Diana; Scheu, Bettina; Wadsworth, Fabian B.; Kennedy, Ben M.; Jolly, Arthur; Dingwell, Donald B.
Abstract: Volcanic lakes are often associated with active geothermal circulation, mineral alteration, and precipitation, each of which can complicate the analysis of shallow magma physics, geophysical signals, and chemical signals. The rheology of the lake and associated hydrothermal system affects the eruptive activity as bubbles ascend and burst through the lake producing distinct ejection behavior. We investigate such phenomena by conducting scaled experiments in which heated water‐clay suspensions are decompressed rapidly from relevant pressures. After a jet phase of expanding vapor, the suspensions break up into ejecta that are either angular or droplet geometry. We parameterize these regimes and find a universal clay volume fraction of 0.28 below which the ejecta are form droplets and above which the ejecta are angular. We propose a regime diagram for optical observations of active lakes, which allows rheological characterization and informs volcanic monitoring. Key Points: A framework to predict the rheology of clay‐rich suspensions in volcanic lakes Quantitative regime boundaries between viscous and brittle eruption behavior in clay suspensions Observations of steam‐driven eruptions through lakes can be diagnostic of clay content